Systematics and evolutionary history of raft and nursery‐web spiders (Araneae: Dolomedidae and Pisauridae) - Yu, Kuang‐Ping; Cheng, Ren‐Chung; Haddad, Charles R.; Tanikawa, Akio; Pett, Brogan L.; Piacentini, Luis N.; Yip, Ho Yin; Suzuki, Yuya; Henrard, Arnaud; Painting, Christina J.; Vink, Cor J.; Hebets, Eileen A.; et al. (Zoologica scripta, 2025)
Pisauridae are a global and heterogeneous assemblage of spider genera with diverse morphologies and lifestyles. So far, the monophyly of Pisauridae and the inclusion of fishing spiders (Dolomedes) in this family have not been thoroughly tested. Here, we amend the systematics and classification of these lineages within a UCE phylogenomic framework and through a detailed morphological reappraisal. For estimations of their evolutionary age, we perform and compare outcomes from two divergence estimation approaches, an a posteriori likelihood, and an a priori Bayesian. Phylogenies reject the monophyly of both Pisauridae and Dolomedes: (1) Focal Clade I groups true Pisauridae genera including Pisaura; (2) Focal Clade II contains Blandinia and is sister to Trechaleidae and Lycosidae; (3) Focal Clade III groups Dolomedes, Megadolomedes, and Ornodolomedes, and is sister to Blandinia, Trechaleidae, and Lycosidae. We therefore propose to delimit Pisauridae by removing Dolomedidae rank resurrected (including Dolomedes, Bradystichus, Megadolomedes, Caledomedes, Mangromedes, Ornodolomedes, and Tasmomedes) and Blandinia incertae sedis. Likelihood and Bayesian time calibration approaches yield comparable divergence estimations: Pisauridae origin is estimated at 29–40 Ma; Blandinia 21–34 Ma; Dolomedidae 10–17 Ma; Dolomedes 9–16 Ma. Reconstructions suggest that the evolution of terrestrial and web‐building lifestyles from semi‐aquatic ancestors in Pisauridae coincided with cooling and drying climates during the mid‐Miocene, but this was not the case in the few recent cases of terrestrialization in Dolomedes species. This historic reconstruction illustrates how climatic changes, or rapid radiation, can drive lifestyle diversification.